Pemahaman Peraturan, Efektivitas Sistem, Kewajiban Moral, Kualitas Pelayanan, Sanksi Perpajakan Pada Kemauan Ikut Tax Amnesty - Suari, Elya Vikana; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2018)
Tax compliance is an attitude or behavior of taxpayers who exercise all their tax obligations and enjoy all the rights of taxation in accordance with the legislation in force.One of the government policies to improve taxpayer compliance is to apply tax amnesty which can be the first step in improving the weakness of taxation situation in Indonesia. Tax amnesty policies have the potential to encourage voluntary tax compliance. The willingness of taxpayers to participate in tax amnesty is important in order to optimize tax revenue. Several factors can affect taxpayer compliance, especially the willingness to participate in tax amnesties that could increase state revenues. The purpose of this study is to examine the effect of understanding tax laws, perceptions of the effectiveness of the tax system, moral obligations, quality of service, and tax sanctions on the willingness of participating tax amnesty. This research was conducted in Tax Office (KPP) Pratama East Denpasar. Population in this study are all effective individual taxpayer in Tax Office(KPP) Pratama East Denpasar. The number of samples in this study were 100 respondents with accidental sampling method. Data collection was conducted by questionnaire technique. Data analysis technique used is multiple linear regression analysis. The results of this study indicate that the understanding of tax laws, perceptions of the effectiveness of the tax system, moral obligations, quality of service, and tax sanctions have a positive effect on the willingness of participating tax amnesty. Keywords:    u nderstanding, effectiveness system, moral obligations, quality of service, tax sanctions, tax amnesty